Collaborative gamified approach for transportation - Major, M.; Ferreira, J.; Maia, R.; Rui Maia; Maia, R.; Rui Maia (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2019)
Transportation-related costs are responsible for a large portion of the logistics cost. This is particularly important in city logistics process where it is not easy to aggregate deliveries. Fleet management if often based on efficiency criteria which does not always is compatible with customers’ service requests. Models supported by ICT, blockchain and gamification tools are developed to raise collaboration and share of resources in urban logistics process, in a kind of “Logistics-as-uber” concept, where operators share resource and ICT system support than giving advice, handle transactions. The discussion is provided on how such a framework can contribute to simultaneously reduce logistics costs, improve service delivery, reduce traffic in cities and reduce pollution.